Eksistensi Perjanjian Ditengah Pandemi Covid-19 - Kunarso Kunarso; A Djoko Sumaryanto (Batulis Civil Law Review, 2020)
Corona Virus Disease-19 (COVID-19) has a significant impact on all aspects of human life in the world, especially in Indonesia which is very large in area and has a large population (around 267 million people) with different kinds of professions. The purpose of this study is to focus on civil matters, with more emphasis on the problem of agreements that are influenced by Covid-19. The normative legal research method uses a statutory approach, and a conceptual approach to force majeure and describes an analysis (analytical descriptive). The results showed that the agreement in the state of the Covid-19 outbreak greatly influenced the implementation of the agreement set and agreed upon by the parties, because the agreement binds the parties, so the parties are subject to the contents of the agreement.